Manajemen konten pada platform instagram Fakultas Pendidikan di Universitas Swasta di Daerah Istimewa Yogyakarta - Imama, Mohammad Luthfi; Hidayati, Dian (Academy of Education Journal, 2024)
This study aims to determine the process of educational promotion content management in one of the education faculties at a private university in Yogyakarta. The research problem focuses on understanding how the social media content management process is carried out by the Instagram account management team of the education faculty of a private university in Yogyakata. This research uses qualitative research which is described descriptively with a case study approach. The results of this study are that in managing new student admission content on Instagram at the education faculty of a private university in Yogyakarta, there are 4 steps taken, namely: planning, organizing, actuating, and controlling. The planning process is carried out through setting goals for using Instagram and creating/taking over accounts. The next process is organizing which is carried out by filling in positions consisting of coordinators, admins, graphic designers, editors, talents, and streaming operators. In the next process, namely mobilizing each position to carry out their duties properly, then the leadership provides enthusiasm or input so that they always work diligently according to the target. The final step is that supervision is carried out through reviews, weekly meetings, and the use of performance statistical analysis tools both on Instagram and through other pages, for example socialblade.